Disparities in Receipt of Radiotherapy and Survival by Age, Sex, and Ethnicity among Patient with Stage I Follicular Lymphoma - Bista, Amir; Sharma, Sandhya; Shah, Binay Kumar (Frontiers in Oncology, 2016)
Background: Radiotherapy (RT) is a first line treatment option for stage I follicular lymphoma. We studied disparities in receipt of radiotherapy and survival among patients with stage I follicular lymphoma. Methods: Adult patients (age ≥18 years) with stage I follicular lymphoma, as the first primary cancer, diagnosed between 1992 and 2007 were identified using Surveillance, Epidemiology and End Results (SEER) 18 database. Study population was divided into various subgroups based on age, sex, race and marital status. Factors associated with receipt of RT and survival, among patients receiving RT, was evaluated using regression analysis and Cox PH modeling respectively. SEER*Stat was used to compute 1 year and 5 year RS for various subgroups and compared using Z score. Results: Of the total 7315 patients (median age: 64 years), 2671 (36.5%) received RT. African Americans, older age group, and single and separated/divorced/widow marital status predicted omission of RT. 1- and 5- year RS were significantly better in patients receiving RT. In multivariate analysis, male sex, age <60 years, Caucasian race and married marital status were found to be independent predictor of better RS among patients receiving RT (P <0.0001). Conclusion: This study showed that 36.5% patients with stage I follicular lymphoma received RT. Survival rates were significantly better for patients who received RT.